Forensic genetics in NGS era: New frontiers for massively parallel typing. (December 2015) - Iozzi, S.; Carboni, I.; Contini, E.; Pescucci, C.; Frusconi, S.; Nutini, A.L.; Torricelli, F.; Ricci, U.
Abstract: Next generation sequencing (NGS) represents the newest approach for massive DNA sequencing. Although this innovative approach is a well-established point in diagnostic genetics, the applicability in forensic field is still limited to sporadic pilot studies. This limit arises from the samples' complexity, in terms of poor quality/quantity ratio, leading to a difficult setting in analytic systems. In this study, first NGS forensic data with a new analytic protocol are presented; data were obtained with a pre-release version of the MiSeq system (Illumina). The system is able to sequence, at the same time, a wide panel including autosomal 63 STRs and 95 SNPs commonly used in forensic practice. In the first part of the study sensitivity and concordance studies were performed by using DNA controls with known genetic profile; also mixtures with different male/female concentrations were analysed, in order to verify the panel performance in comparison with traditional kits. In the second part of the experiment, 60 casework samples coming from different tissues, biological fluids, traces on supports, lysates, different aged/degraded samples were analysed. Bioinformatic analysis was performed with MiSeq FGx System BETA version (Illumina), an innovative software with an easy interface that permits a rapid data interpretation by filtering the big data quantity generated by the instrument. The comparison between new data and genetic profiles obtained with traditional typing on the same samples, the sensitivity and the potential of NGS approach represents an interesting starting point in introducing this innovative approach on forensic genetics scenario.